2017
DOI: 10.1016/j.applthermaleng.2016.12.122
|View full text |Cite
|
Sign up to set email alerts
|

HEM and HRM accuracy comparison for the simulation of CO2 expansion in two-phase ejectors for supermarket refrigeration systems

Abstract: In this study, the accuracies of the homogeneous equilibrium (HEM) and homogeneous relaxation models (HRM) were compared. Both models were implemented in the ejectorPL computational tool. The HEM and HRM were used to simulate the carbon dioxide flow in ejectors that were designed for supermarket refrigeration systems. The model accuracy was evaluated by comparing the computational results with the experimental data. The discrepancy between the measured and computed motive nozzle mass flow rates was analysed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…This means that the model correctly reproduces the tendency of a near-critical flow to become closer to an equilibrium phase change. Similar conclusions were found by Palacz et al [33] by comparing the results obtained with a HEM and an HRM.…”
Section: Mass Flow Ratessupporting
confidence: 90%
“…This means that the model correctly reproduces the tendency of a near-critical flow to become closer to an equilibrium phase change. Similar conclusions were found by Palacz et al [33] by comparing the results obtained with a HEM and an HRM.…”
Section: Mass Flow Ratessupporting
confidence: 90%
“…They developed a widely excepted correlation for relaxation time considering the critical flow parameters, vapor quality, and temperature profile. Through a comparison study, Palacz et al [92] found that HRM could predict the flow characteristics better than HEM (overall a 5% increase in accuracy). In addition, Zheng et al [93] and He et al [94] proposed dynamic numerical models, which are useful in predicting the dynamic system response in different operating conditions to optimize the ejector expansion performance.…”
Section: Expansion Devicementioning
confidence: 99%
“…The turbulent dynamic viscosity and turbulent thermal conductivity, which appeared in eq. (6) and 7, were calculated by applying formulae relevant for used turbulence model.…”
Section: Turbulence Modellingmentioning
confidence: 99%
“…Successful validation procedure was also carried out by comparing obtained results with the experimental data for the primary and secondary mass flow rates in the ejector device as well as the pressure at the selected points in the computational domain. Next, Palacz et al [6] proposed a more complex two-phase flow model of the CO2 ejector, i.e., the HRM which included metastable effects. Then they evaluated the accuracy of the new model against the previously proposed HEM [5] by comparing calculated results with the experimental data for the typical operating regimes of CO2-based refrigeration systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation